The enhanced recovery program in urology. Systematic review and meta-analysis - Vorobev, V. A.; Beloborodov, V. A.; Tukhiev, A. R. (Acta biomedica scientifica, 2023)
A systematic review and meta-analysis of data on the problem of enhanced recovery in urology was performed. Inclusion criteria – clinical trials of the enhanced recovery program in urology. The aim of the study was to assess the significance of the enhanced recovery program (ERP) in the provision of surgical care in the “urology” profile. Materials and methods . The systematic review was performed according to the guidelines for the presentation of systematic reviews and meta-analyses by PRISMA. The registration number in the international system Prospero was received (CRD42022358982). The review included 364 studies. Studies in urologic oncology were excluded from the meta-analysis. The meta-analysis included 15 studies involving 2293 subjects. A comparison was made between the application of ERP and the standard treatment protocol. Results. The use of ERP leads to an expected two-fold reduction in the duration of postoperative length of hospitalization (OR = –1.96; 95% CI: –2.56÷–1.36; p < 0.00001). The reduction in the duration of hospitalization with the use of ERP in urology does not lead to the increased risk of readmission or re-operation (p = 0.35). The risks of developing postoperative complications ≥ Class 2 by Clavien – Dindo classification were comparable in both groups (p = 0.13). The use of ERP increases the expected success of the treatment by 1.74 times (OR = 1.74; 95% CI: 1.08–2.79; p = 0.02). With the use of ERP in reconstructive urology, a significantly lower risk of complications was established (p = 0.02). Conclusion. The ERP program allows you to reduce the time and cost of treatment, reduce the likelihood of re-hospitalization and achieve better treatment results. The use of ERP is not accompanied by increased risk of complications > Class 2.